Genome-wide analysis in UK Biobank identifies four loci associated with mood instability and genetic correlation with major depressive disorder, anxiety disorder and schizophrenia. Issue 11 (November 2017) - Ward, Joey; Strawbridge, Rona; Bailey, Mark; Graham, Nicholas; Ferguson, Amy; Lyall, Donald; Cullen, Breda; Pidgeon, Laura; Cavanagh, Jonathan; Mackay, Daniel; Pell, Jill; O'Donovan, Michael; et al.
Abstract Mood instability is a core clinical feature of affective and psychotic disorders. In keeping with the Research Domain Criteria approach, it may be a useful construct for identifying biology that cuts across psychiatric categories. We aimed to investigate the biological validity of a simple measure of mood instability and evaluate its genetic relationship with several psychiatric disorders, including major depressive disorder (MDD), bipolar disorder (BD), schizophrenia, attention deficit hyperactivity disorder (ADHD), anxiety disorder and post-traumatic stress disorder (PTSD). We conducted a genome-wide association study (GWAS) of mood instability in 53, 525 cases and 60, 443 controls from UK Biobank, identifying four independently associated loci (on chromosomes 8, 9, 14 and 18), and a common single-nucleotide polymorphism (SNP)-based heritability estimate of 8%. We found a strong genetic correlation between mood instability and MDD (r g = 0.60, SE = 0.07, p = 8.95 × 10−17 ) and a small but significant genetic correlation with both schizophrenia (r g = 0.11, SE = 0.04, p = 0.01) and anxiety disorders (r g = 0.28, SE = 0.14, p = 0.04), although no genetic correlation with BD, ADHD or PTSD was observed. Several genes at the associated loci may have a role in mood instability, including theDCC netrin 1 receptor (DCC ) gene, eukaryotic translation initiation factor 2B subunit beta (eIF2B2 ), placental growth factor (PGF ) andprotein tyrosine phosphatase, receptor type D (PTPRD ). Strengths of this study include the very large sample size, but our measure of mood instability may be limited by the use of a single question. Overall, this work suggests a polygenic basis for mood instability. This simple measure can be obtained in very large samples; our findings suggest that doing so may offer the opportunity to illuminate the fundamental biology of mood regulation.